2023
DOI: 10.1200/po.23.00037
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Chromosome 3q Is a Prognostic Marker in Fusion-Negative Rhabdomyosarcoma

Carina A. Dehner,
Robert C. Bell,
Yang Cao
et al.

Abstract: We show that loss of chr3q is associated with worse outcomes in fusion-negative (FN)-RMS compared with fusion-positive (FP)-RMS, suggesting that this chromosomal abnormality could be a prognostic marker for (FN) RMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recently, significant progress was made in understanding the genetic and epigenetic factors associated with RMS (12). Numerous studies on RMS have identified new diagnostic and prognostic markers that have led to the development of novel therapeutic strategies (13). ROS have been identified as significant targets in highthroughput drug-screening assays (2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, significant progress was made in understanding the genetic and epigenetic factors associated with RMS (12). Numerous studies on RMS have identified new diagnostic and prognostic markers that have led to the development of novel therapeutic strategies (13). ROS have been identified as significant targets in highthroughput drug-screening assays (2).…”
Section: Discussionmentioning
confidence: 99%